Beyond the Screen: An Interpretative Phenomenological Analysis of Undergraduate Students' Speaking Anxiety Under Strict Technological Deprivation - Abdurrohman Septiadi; Riskayadi (Universitas Islam Negeri Palopo, 2026)
Most research on foreign language speaking anxiety has examined it through classroom anxiety scales, public-speaking contexts, or, more recently, online and AI-mediated learning; comparatively little is known about what happens when digital tools are deliberately withdrawn. This study explores how ten undergraduate students in Bangka Belitung Province experienced speaking anxiety during structured English-speaking activities conducted under strict technological deprivation, defined as the intentional, sustained removal of smartphones, chatbot applications, and internet access during a speaking task. Using Interpretative Phenomenological Analysis (IPA), semi-structured interviews were analyzed idiographically before cross-case synthesis, following Smith and Osborn's procedure. Rather than converging on a single tidy narrative, participants' accounts diverged in intensity, trajectory, and meaning. Five superordinate themes emerged: (1) digital concealment and the fear of being